Analisis Jaringan Kerja Dengan Metode Critical Path Method (CPM) Pembangunan Rumah Type 36 Pada PT. Arisko Di Sambutan Samarinda - Muhammad Rhino Rakadhipa; Anis Rachma Utary; Rizky Yudarrudin (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
Muhammad Rhino Rakadhipa, 2017. Analysis Network Work With Critical Path Methode (CPM) Development of House of Type 36 at PT. Arisko in Greeting of Samarinda. Under direction of: Mrs. Hj. Anis Rachma Utary and Mr. Rizky Yudaruddin. This Research aim to know optimal 55 time workday development of house of type 36 woke up by PT. Arisko in Greeting of Samarinda. This Research use method of Critical Path Methode (CPM). Data in this research come from schedule is project of and RAB (Cost Estimate Expense) made by PT. Arisko. gathered to be Data to be analysed to use searched by last CPM of critical trajectory him use network activity, after obtained by maximum deadline of project hereinafter the project of quickened to use CPM. Pursuant to result of calculation use CPM, planning of time is project of development of house of type 36 by PT. Arisko have efficient enough. This matter seen from opportunity of attainment of time goals is solving of the project of which is expected by company that is 55 workday become 54 workday. But delay in solving of the project of development can overcome by using CPM. Result of calculation of CPM menunjukan old age the project of shorter that is 54 workday however requiring surcharger equal to Rp. 8.890.000,00 Keyword : Critical Path Method, Network Activity